Evaluating the effect of an educational program on increasing cervical cancer screening behavior among rural women in Guilan, Iran - Sedighe Bab Eghbal; Mahmood Karimy; Parisa Kasmaei; Zahra Atrkar Roshan; Roghieh Valipour; Seyedeh Maryam Attari (BMC, 2020)
Abstract Background Cervical cancer is one of the major health problems and the third prevalent cancer in women all around the world. As a simple, inexpensive, and with no side-effects, Pap test is a reliable way to screen cervical cancer. This study aimed to investigate, the effects of educational intervention based on the Health Belief Model (HBM) on doing Pap smear tests among the rural women of the north of Iran. Methods In a quasi-experimental study, 160 rural women were randomly divided into control and experimental groups to experience a three-session intervention. The experimental group received the usual educational programs of rural health center and educational programs based on the HBM constructs through personal consultation, asking/answering questions, and an educational pamphlet. The control group, received the usual educational programs of rural health center. The post-test data were collected 2 months after the intervention and analyzed in SPSS-18. Results Before the intervention, there was no significant difference between the control and experimental groups regarding the mean score of knowledge, performance and constructs of the HBM. After the intervention, however, there was a significant difference in the mean scores of knowledge performance and all constructs of the HBM in two groups (p < 0.001). Rate of doing the Pap smear test in the experimental group increased from 18.7 to 78.7% in the intervention group. Conclusion These findings support the effectiveness of cervical cancer prevention programs based on the HBM. Therefore, conducting similar programs in other regions is recommended.